Effect of dietary concentrate content on feed intake, feed efficiency, and meat quality of Holstein steers fattened in a hot environment. (30th March 2021) - Alqaisi, Othman; Ali, Haytham; Al‐Abri, Mohammad; Johnson, Eugene H.; Al‐Marzooqi, Waleed
Abstract: The objective of this study was to investigate the effect of feeding high and low concentrate diets on feed intake and feed efficiency, the morphological characteristics of the rumen papillae, and meat quality of Holstein steers fattened under hot climate conditions in Oman. Ten male Holstein calves, of 5 months of age, were selected for the experiment. The animals were fed concentrate and Rhodes grass hay and were divided into two groups of high concentrate (HC, n  = 5) and low concentrate diets (LC, n  = 5), in which their feed intake, weight gain, and feed efficiency were evaluated across three growing periods. Feed intake and efficiency and average daily gain (ADG) of the HC group were significantly greater than for the LC group and were affected by the diet ( p  < .01) and the period ( p  < .001). Across the fattening periods, ADG declined in both groups, with ADG improved by 35% for steers on the HC diet compared to steers on the LC diet. Carcass meat quality was not affected significantly by the dietary concentrate level. In conclusion, our results can be used to make improvements in feed efficiency of Holstein steers under hot climate conditions.